2007
DOI: 10.1002/chem.200601699
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzing Aldehyde Hydrosilylation with a Molybdenum(VI) Complex: A Density Functional Theory Study

Abstract: [MoCl(2)O(2)] catalyzes the hydrosilylation reaction of aldehydes and ketones, as well as the reduction of other related groups, in apparent contrast to its known behavior as an oxidation catalyst. In this work, the mechanism of this reaction is studied by means of density functional theory calculations using the B3LYP functional complemented by experimental data. We found that the most favorable pathway to the first step, the Si--H activation, is a [2+2] addition to the Mo=O bond, in agreement with previous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 37 publications
0
44
2
1
Order By: Relevance
“…This new methodology has the advantage of using the air-stable oxo complex MoO 2 Cl 2 (H 2 O) 2 as the catalyst, which has an easy and inexpensivep reparation by extraction from ah ydrochlorica cid solution of Na 2 MoO 4 with diethyl ether. [16] We propose that the mechanism for the deoxygenation of the aryl ketones to the corresponding alkenes with the catalytic system of PhSiH 3 / MoO 2 Cl 2 (H 2 O) 2 involves the formation of ah ydride species, which results from SiÀHb ond activation of the silane by the oxo molybdenumc omplex as demonstrated in our previousw ork, [17] followed by the reductiono ft he ketone to the corresponding alcohol. If phenylsilane is used as the reducing agent, the major product obtained in the reduction of the ketone is the alcohol and not www.chemcatchem.org the silyl ether,p robablyb ecause of the instability of the silyl ether formed from this silane.Finally,the dehydration of the alcohol to the alkene occurs.…”
Section: Resultsmentioning
confidence: 77%
“…This new methodology has the advantage of using the air-stable oxo complex MoO 2 Cl 2 (H 2 O) 2 as the catalyst, which has an easy and inexpensivep reparation by extraction from ah ydrochlorica cid solution of Na 2 MoO 4 with diethyl ether. [16] We propose that the mechanism for the deoxygenation of the aryl ketones to the corresponding alkenes with the catalytic system of PhSiH 3 / MoO 2 Cl 2 (H 2 O) 2 involves the formation of ah ydride species, which results from SiÀHb ond activation of the silane by the oxo molybdenumc omplex as demonstrated in our previousw ork, [17] followed by the reductiono ft he ketone to the corresponding alcohol. If phenylsilane is used as the reducing agent, the major product obtained in the reduction of the ketone is the alcohol and not www.chemcatchem.org the silyl ether,p robablyb ecause of the instability of the silyl ether formed from this silane.Finally,the dehydration of the alcohol to the alkene occurs.…”
Section: Resultsmentioning
confidence: 77%
“…[8,9] Other oxomolybdenum complexes have been used for epoxidations [10] and reductions of sulfoxides and alkenes. [11] Molybdenum-catalyzed reactions that have previously been studied by computational methods include oxidations, [12] hydrosilylations, [13] and reductions using either hydrogen [11h] or silanes. [14] In line with earlier work, [15][16][17] we have carried out a computational study using density functional theory (DFT) to clarify the mechanism of the molybdenum-catalyzed DODH.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies performed for this reaction have also suggested a radical mechanism (Fig. 76) [49]. This study demonstrated that after the formation of hydrogen radicals, they could add to aldehyde, forming an alkoxyl radical, which can combine with Fig.…”
Section: Hydrosilylation Of Carbonyl Compoundsmentioning
confidence: 93%
“…A mechanism for the hydrosilylation of aldehydes and ketones catalyzed by MoO 2 Cl 2 (1) was proposed based on computational studies [49]. We found that the most favorable pathway to the first step, the Si-H activation, is a [2+2] addition to the Mo=O bond, forming the hydride species MoCl 2 H(O)(OSiR 3 ) H (Fig.…”
Section: Hydrosilylation Of Carbonyl Compoundsmentioning
confidence: 95%
See 1 more Smart Citation